2018
DOI: 10.1038/s41598-018-27426-w
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio inspired design of ternary boride thin films

Abstract: The demand to discover new materials is scientifically as well as industrially a continuously present topic, covering all different fields of application. The recent scientific work on thin film materials has shown, that especially for nitride-based protective coatings, computationally-driven understanding and modelling serves as a reliable trend-giver and can be used for target-oriented experiments. In this study, semi-automated density functional theory (DFT) calculations were used, to sweep across transitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 50 publications
3
31
0
Order By: Relevance
“…[13][14][15][16][17] Recently, TM diborides have been receiving increasing attention as the next generation of refractory, hard ceramic protective thin films for replacing TM nitrides in many applications. [18][19][20][21] TM diborides are already being employed as coatings on cutting tools [22][23][24][25] and engine components, [26][27][28] as well as for use as diffusion barriers in microelectronics. [29][30][31] While TM diborides are inherently hard, that alone is not sufficient to prevent failure in applications involving high stresses, since hardness is typically accompanied by brittleness leading to crack formation and propagation.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17] Recently, TM diborides have been receiving increasing attention as the next generation of refractory, hard ceramic protective thin films for replacing TM nitrides in many applications. [18][19][20][21] TM diborides are already being employed as coatings on cutting tools [22][23][24][25] and engine components, [26][27][28] as well as for use as diffusion barriers in microelectronics. [29][30][31] While TM diborides are inherently hard, that alone is not sufficient to prevent failure in applications involving high stresses, since hardness is typically accompanied by brittleness leading to crack formation and propagation.…”
Section: Introductionmentioning
confidence: 99%
“…These cermet coatings have already been applied to wear-and corrosion-resistant applications such as injection molding machine parts, bearings for sea water pumps, and offshore engineering parts [9]. In particular, as emerging and promising materials with superior strength, hardness, and wear and corrosion resistance, M 3 B 2 -type boride-based cermet coatings such as Mo 2 FeB 2 , Mo 2 NiB 2 , and W 2 NiB 2 as hard phases, are qualified candidates for applications in wear and corrosion resistance [10,11]. Takagi et al [12] found that M 3 B 2 (Mo 2 FeB 2 and Mo 2 NiB 2 )-based cermet coatings possessed excellent hardness and bonding properties, wear resistance, and corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%
“…In general, materials performance may be improved by synthesis of multicomponent systems, which allows tuning of the properties and control of the microstructure, resulting in overall enhanced functionality [10,11]. Various ternary systems of transition metal diborides are explored in order to obtain superior properties, e.g., W1−xTaxB2−z for a combination of both mechanical strength and ductility [12,13]. An example for hardcoating applications is Ti1-xAlxN, where Ti in TiN is partially replaced by Al, leading to age hardening effect through isostructural clustering, a primary reason behind its success [14].…”
Section: Introductionmentioning
confidence: 99%